Activation of Central Pain Pathways in Rheumatic Diseases: What We have Learned from Functional Neuroimaging Studies - Sofat, Nidhi; Hamann, Philip; R. Barrick, Thomas; A. Howe, Franklyn (Current Rheumatology Reviews, 2010)
Pain is a major symptom in rheumatic diseases. Understanding the nature of patients' pain symptoms in a rheumatology setting is integral to their assessment and optimising care. In recent years we have increasingly come to appreciate that not only is pain dependent on the underlying pathological process, but is also influenced by a number of additional factors that include genetics, the environment of the individual, previous pain experience and psychological status. Although local inflammation in the joint leads to the release of pro-inflammatory mediators including prostaglandins and cytokines that activate nociceptive signals in the joint, recent work has suggested that central activation of the brain is also important in mediating chronic pain in a number of rheumatic conditions including rheumatoid arthritis, fibromyalgia, osteoarthritis and back pain. A number of imaging modalities have been utilized in recent years to gain a deeper understanding of the pathways involved in the perception of pain in the rheumatic diseases. Functional Magnetic Resonance Imaging (fMRI), has been used to assess how the brain responds to and also mediates pain in the presence of arthritic disease. Positron emission tomography (PET) and Single photon emission computed tomography (SPECT) can produce blood flow images of the brain, or with the appropriate choice of radiopharmaceutical can also be used to image metabolic activity or specific neuroreceptors. Magnetoencephalography (MEG) can map cortical brain activity with high temporal resolution. These techniques have shown altered regional cerebral blood flow in areas of the brain in rheumatoid arthritis and fibromyalgia and have been used to determine pathways implicated in the perception of pain in specific conditions including complex regional pain syndrome and fibromyalgia. The information gained from functional imaging studies has improved our understanding of pain perception in rheumatic diseases and so may aid a more effective treatment for pain as will be discussed further in this review.
Keywords: fibromyalgia